A comparison of muscle activity in using touchscreen smartphone among young people with and without chronic neck–shoulder pain. Issue 1 (2nd January 2016) - Xie, Yanfei; Szeto, Grace P.Y.; Dai, Jie; Madeleine, Pascal
Abstract : This study aimed to examine differences in muscle activity between young people with and without neck–shoulder pain ( n  = 20 in each group), when they performed texting on a smartphone. Texting was compared between using both hands ('bilateral texting') and with only one hand ('unilateral texting'). Texting tasks were also compared with computer typing. Surface electromyography from three proximal postural muscles and four distal hand/thumb muscles on the right side was recorded. Compared with healthy controls, young people with neck–shoulder pain showed altered motor control consisting of higher muscle activity in the cervical erector spinae and upper trapezius when performing texting and typing tasks. Generally, unilateral texting was associated with higher muscle loading compared with bilateral texting especially in the forearm muscles. Compared with computer typing, smartphone texting was associated with higher activity in neck extensor and thumb muscles but lower activity in upper and lower trapezius as well as wrist extensors. Abstract : Practitioner Summary : This study demonstrated that symptomatic individuals had increased muscle activity in the neck–shoulder region when texting on a smartphone. Contemporary ergonomic guidelines should include advice on how to interact with handheld electronic devices to achieve a relaxed posture and reduced muscle load in order to reduce the risk of musculoskeletal disorders.